Unveiling the Journey to Community Reintegration: Results from a Qualitative Study with Sexual Offenders on Parole - Cardoso, Ana Rita (International journal of offender therapy and comparative criminology, 2025)
After serving a prison sentence, sex offenders embark on a community reintegration process, where they usually face several barriers that might negatively affect their successful return to society. Results from semi-structured interviews conducted with sex offenders revealed that participants perceive the economic difficulties, the nature of the crime, and the stigma as the main social factors hindering their community reintegration process. Additionally, prison and parole support are described as insufficient, lacking focus on the specific needs of the participants to act as an effective help. On the contrary, housing and affective relationships were not perceived as major obstacles to a successful reintegration. These findings highlight the need for policies that promote economic opportunities, reduce stigma, and enhance both prison-based and post-release support to facilitate a more effective reintegration process.